330 INTRAVENOUS CANGRELOR INFUSION IN HIGH BLEEDING RISK PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTION: PRELIMINARY RESULTS OF THE ICARUS REGISTRY. (15th December 2022) - Benenati, Stefano; Gragnano, Felice; Scalamera, Riccardo; Bertero, Edoardo; Capolongo, Antonio; Sio, Vincenzo De; Musumeci, Giuseppe; Annibali, Gianmarco; Campagnuolo, Salvatore; Galasso, Gennaro; Silverio, Angelo; Bellino, Michele; et al.
Abstract: Aims: To investigate the prevalence of high bleeding risk (HBR) criteria and compare clinical outcomes between HBR and non-HBR patients receiving cangrelor in the peri-percutaneous coronary intervention (PCI) phase. Methods: Consecutive patients treated with cangrelor in 7 Italian institutions were retrospectively enrolled in the ICARUS ("Intravenous CAngrelor in high-bleeding Risk patients Undergoing percutaneouS coronary intervention", NCT05505591) registry. HBR status was assessed according to the Academic Research Consortium (ARC-HBR) definition. The primary endpoint was net adverse clinical events (NACE), defined as a composite of cardiovascular death, myocardial infarction, stroke, definite or probable stent thrombosis and Bleeding Academic Research Consortium (BARC) 2, 3 or 5 bleeding, at 48 hours. Secondary endpoints were assessed at 48 hours and throughout the hospital stay. Results: We enrolled 551 patients undergoing PCI with cangrelor between January 2019 and August 2022. HBR definition was met in 33% of cases. HBR patients were older (76±10 vs. 63±10 years, p<0.001), more frequently affected by peripheral arterial disease (16% vs. 8%, p=0.010), atrial fibrillation (24% vs. 2%, p<0.001), chronic kidney disease (35% vs. 3%, p<0.001), active cancer (7% vs. 0%, p<0.001) and heart failure (17% vs. 7%, p<0.001). At 48 hours, HBR patients had a significantly higher rate of NACE (13% vs. 6%, p=0.004), and BARC 2, 3 or 5 bleeding (12% vs. 4%, p=0.001). In the HBR group, the frequency of the primary endpoint increased proportionally to the HBR score. There was no significant difference with respect to other 48-hour and in-hospital endpoints. Conclusions: Among consecutive patients treated with cangrelor in the peri-PCI phase, about 30% fulfilled the ARC-HBR definition. In the HBR subpopulation, the incidence of 48-hour adverse events was higher than in the non-HBR subgroup, primarily driven by a higher rate of clinically relevant and major bleeding.